2020
DOI: 10.1016/j.eclinm.2020.100525
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate use of convalescent plasma for treatment of moderate and severe pneumonia in COVID-19 patients and association with IgG antibody levels in donated plasma

Abstract: Background: We assessed outcome of patients with moderate and severe COVID-19 following treatment with convalescent plasma (CP) and the association with IgG levels in transfused CP. Methods: A prospective cohort study. Primary outcome was improvement at day 14 defined as alive, not on mechanical ventilation, and moderate, mild, or recovered from COVID-19. Antibody levels in CP units were unknown at the time of treatment. IgG against the spike protein S1 was subsequently measured by ELISA. Neutralizing antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 27 publications
4
71
0
Order By: Relevance
“…Limited previous clinical experiences with CP treatment in SARS-CoV, MERS, influenza, and Ebola suggest that CP may provide benefits to COVID-19 patients (Bloch et al, 2020;Devasenapathy et al, 2020). Many recent reports have documented clinical outcomes of CP treatment in severe and critically ill COVID-19 patients (Ahn et al, 2020;Ibrahim et al, 2020;Jin et al, 2020;Keith et al, 2020;Li et al, 2020a;Li et al, 2020b;Liu et al, 2020a;Madariaga et al, 2020;Maor et al, 2020;Pei et al, 2020;Perotti et al, 2020;Dwi Putera and Suci Hardianti, 2020;Shen et al, 2020a;Wang et al, 2020c;Ye et al, 2020a;Zhang et al, 2020a). Two categories of results are presented.…”
Section: Convalescent Plasma and Ivig Treatment Of Covid-19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited previous clinical experiences with CP treatment in SARS-CoV, MERS, influenza, and Ebola suggest that CP may provide benefits to COVID-19 patients (Bloch et al, 2020;Devasenapathy et al, 2020). Many recent reports have documented clinical outcomes of CP treatment in severe and critically ill COVID-19 patients (Ahn et al, 2020;Ibrahim et al, 2020;Jin et al, 2020;Keith et al, 2020;Li et al, 2020a;Li et al, 2020b;Liu et al, 2020a;Madariaga et al, 2020;Maor et al, 2020;Pei et al, 2020;Perotti et al, 2020;Dwi Putera and Suci Hardianti, 2020;Shen et al, 2020a;Wang et al, 2020c;Ye et al, 2020a;Zhang et al, 2020a). Two categories of results are presented.…”
Section: Convalescent Plasma and Ivig Treatment Of Covid-19 Patientsmentioning
confidence: 99%
“…Among the above studies, 11 reported CP treatment in 10 or less COVID-19 patients (Ahn et al, 2020;Duan et al, 2020;Jin et al, 2020;Keith et al, 2020;Li et al, 2020a;Madariaga et al, 2020;Pei et al, 2020;Shen et al, 2020a;Wang et al, 2020c;Ye et al, 2020a;Zhang et al, 2020a). Five studies treated 37-49 patients (Ibrahim et al, 2020;Liu et al, 2020a;Maor et al, 2020;Perotti et al, 2020;Dwi Putera and Suci Hardianti, 2020). Only one randomized trial wherein 52 patients received CP treatment was reported and the results demonstrated that CP therapy plus standard treatment in severe or life-threatening COVID-19 patients did not result in significant clinical improvement (Li et al, 2020b).…”
Section: Convalescent Plasma and Ivig Treatment Of Covid-19 Patientsmentioning
confidence: 99%
“…Although neutralizing antibodies can be difficult to quantify outside of a laboratory setting, recent work shows that IgG levels correlate well with neutralizing antibody levels [ 56 ]. Levels of antibodies are measured using dilution factors; convalescent plasma should have a titer higher than 1:160, but the range of neutralizing antibody concentrations in convalescent plasma can be from 1:60 to 1:2650 [ 56 , 57 ]. Neutralizing antibody levels could offer a method to screen potential donors through quantification of levels of IgG.…”
Section: Serostatus and Immunitymentioning
confidence: 99%
“…Interestingly, convalescent plasma therapy has proven to be beneficial in B-cell depleted patients having protracted COVID-19 [ 33 ], with an acknowledged limit inherent to uncontrolled observations [ 34 ]. Compassionate plasma therapy was applied early in the disease course [ [35] , [36] , [37] ]. As many more RCTs or compassionate programs are run in major healthcare facilities or within international consortiums, regulatory bodies—such as the FDA—also made more precise recommendations [ 38 ].…”
mentioning
confidence: 99%